2018
DOI: 10.3389/fpsyg.2018.01392
|View full text |Cite
|
Sign up to set email alerts
|

Confronting a Paradox: A New Perspective of the Impact of Uncertainty in Suspense

Abstract: Suspense is a key narrative issue in terms of emotional gratifications. Reactions in response to this type of entertainment are positively related to enjoyment, having a significant impact on the audience's immersion and suspension of disbelief. Related to computational modeling of this feature, some automatic storytelling systems include limited implementations of suspense management system in their core. In this way, the interest of this subject in the area of creativity has resorted to different definitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…In narratology, uncertainty over outcomes is traditionally seen as suspenseful (e.g., O'Neill, 2013;Zillmann, 1996;Abbott, 2008). Other authors claim that suspense can exist without uncertainty (e.g., Smuts, 2008;Hoeken and van Vliet, 2000;Gerrig, 1989) and that readers feel suspense even when they read a story for the second time (Delatorre et al, 2018), which is unexpected if suspense is uncertainty; this is referred to as the paradox of suspense (Prieto-Pablos, 1998;Yanal, 1996). Considering Romeo and Juliet again, in the first view suspense is motivated by primarily by uncertainty over what will happen.…”
Section: Related Workmentioning
confidence: 99%
“…In narratology, uncertainty over outcomes is traditionally seen as suspenseful (e.g., O'Neill, 2013;Zillmann, 1996;Abbott, 2008). Other authors claim that suspense can exist without uncertainty (e.g., Smuts, 2008;Hoeken and van Vliet, 2000;Gerrig, 1989) and that readers feel suspense even when they read a story for the second time (Delatorre et al, 2018), which is unexpected if suspense is uncertainty; this is referred to as the paradox of suspense (Prieto-Pablos, 1998;Yanal, 1996). Considering Romeo and Juliet again, in the first view suspense is motivated by primarily by uncertainty over what will happen.…”
Section: Related Workmentioning
confidence: 99%
“…Part of these observations are in line with the general idea of suspense found in the relevant literature (Delatorre et al, 2016b): although the existing multiple definitions of suspense largely differ in the identification and importance of its fundamental features 1 (see Zillmann and Tannenbaum, 1980; Carroll, 1984; Ortony et al, 1990; Caplin and Leahy, 2001; Vorderer et al, 2001; Somanchi, 2003; Szilas, 2007; Abbott, 2008; Smuts, 2008, among others), there is a general agreement that suspense is triggered by the anticipation of an outcome which is mostly negative for the characters (Delatorre et al, 2018). This conceptualization can be found, for instance, in the definition by de Wied et al (1992, p. 325), that describe(s) suspense as “an anticipatory emotion, initiated by an event which sets up anticipations about a forthcoming (harmful) outcome event for one of the main characters.” Such a common approach seems consistent with the values of the affective dimensions reported by the participants of the aforementioned experiment: decreased valence and dominance, and increased arousal.…”
Section: Introductionmentioning
confidence: 99%
“…Delatorre et al () report an experiment where participants were shown a simple story displayed as a sequence of slides on a computer screen. The plot was whether a replacement organ would arrive in time to save the life of a dying child.…”
mentioning
confidence: 99%